Belgium and the Brussels Question: The Role of Non-Territorial Autonomy. Issue 1 (1st January 2016) - Dalle Mulle, Emmanuel
Abstract: This article describes and assesses the process of territorial and non-territorial devolution in Belgium. After providing a description of the linguistic structure of the country and the background that led to its transformation from a unitary consociational democracy to a federal one mixing forms of territorial and non-territorial autonomy, it provides an assessment of the functioning of non-territoriality in Brussels and its capacity to accommodate linguistic diversity and conflict. It concludes with an overall positive assessment, since the solution that was reached allowed linguistic conflict to be kept at a tolerable level and granted a substantial degree of autonomy to each linguistic community. Nevertheless, the Belgian case also points to some problems. First, non-territorial autonomy has mainly been based on a system of dual monolingualism rather than true bilingualism, and this has contributed to separation between the two communities and to the centrifugal forces unleashed since the linguistic territorialisation of Flanders and Wallonia. Second, because of the coexistence of territorial and non-territorial autonomy, the definition of the border of the non-territorial area has been problematic and contested. This has favoured the persistence of conflict, though concentrated on the border between the two areas; but it has not escalated into expressions of violence.